Cover Feature: Syntheses, Structural Characterization, and Kinetic Investigations of Metalla[3]triangulanes: Isoelectronic Nickel(0) and Copper(I) Complexes with Bicyclopropylidene (bcp) and Dicyclopropylacetylene (dcpa) as Ligands (12/2021). Issue 12 (4th March 2021) - Ritz, Florian J.; Valentin, Lars; Henß, Anja; Würtele, Christian; Walter, Olaf; Kozhushkov, Sergei I.; de Meijere, Armin; Schindler, Siegfried
Abstract : The Cover Feature shows the alkene Bicyclopropylidene (bcp) that became (as well as its derivatives) a versatile C6 building blocks for organic synthesis. It can undergo co‐cyclizations under palladium, nickel, and cobalt catalysis. However, despite the fundamental interest in the mechanism of these reactions, so far only a small number of transition metal complexes with bcp as ligand have been isolated and structurally characterized. Herein, we report the molecular structures of the nickel and copper complexes – [Ni(bipy)(bcp)] [Cu(bipy)(bcp)]PF6 (anion not shown) – with bcp and 2, 2′‐bipyridine as a co‐ligand. More information can be found in the Full Paper by A. de Meijere, S. Schindler et al.